Elevated Serum Retinol Binding Protein 4 is Associated with the Risk of Diabetic Cardiomyopathy - Haihua Shan (Reviews in Cardiovascular Medicine, 2022)
Background: Retinol binding protein 4 (RBP4), a biomarker for insulin resistance in type 2 diabetes (DM), is increased in heart failure. This case-control study aims to determine the association between serum RBP4 levels and diabetic cardiomyopathy (DCM). Methods: Demographic and clinical data were obtained from 245 DM patients and 102 non-diabetic controls. RBP4 levels were measured using ELISA. The association between RBP4 and DCM was evaluated using multivariate logistic regression and restricted cubic splines (RCS) in DM patients. Results: We showed that serum RBP4 levels were higher in DCM patients than in DM patients without DCM or the controls. Multivariate analysis adjusted by age, gender, body mass index, diabetes duration, left ventricular ejection fraction, insulin treatment, triglycerides, low-density lipoprotein cholesterol, estimated glomerular filtration rate, diabetic retinopathy, diabetic nephropathy, diabetic neuropathy and log N-terminal proBNP showed a significant association between RBP4 and DCM (highest vs. lowest tertile OR 16.87, 95% CI: 6.58, 43.23, p < 0.001). RCS displayed a positive linear correlation between RBP4 levels and the risk of DCM in diabetes (p = 0.004). Adding RBP4 to a basic risk model for DCM improved the reclassification (Net reclassification index: 87.86%, 95% CI: 64.4%, 111.32%, p < 0.001). Conclusions: The positive association between serum RBP4 and DCM suggested the role of RBP4 as a potential diagnostic biomarker for distinguishing DCM in patients with DM.